2020
DOI: 10.1371/journal.pone.0244207
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative efficacy of selenate and selenium nanoparticles for improving growth, productivity, fruit quality, and postharvest longevity through modifying nutrition, metabolism, and gene expression in tomato; potential benefits and risk assessment

Abstract: This study attempted to address molecular, developmental, and physiological responses of tomato plants to foliar applications of selenium nanoparticles (nSe) at 0, 3, and 10 mgl-1 or corresponding doses of sodium selenate (BSe). The BSe/nSe treatment at 3 mgl-1 increased shoot and root biomass, while at 10 mgl-1 moderately reduced biomass accumulation. Foliar application of BSe/nSe, especially the latter, at the lower dose enhanced fruit production, and postharvest longevity, while at the higher dose induced m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(31 citation statements)
references
References 35 publications
0
31
0
Order By: Relevance
“…However, the mechanism through which ZnO-NP is capable of conferring partly differential responses remains controversial. A majority of researchers believe that differential physicochemical characteristics of nanoparticles relative to the bulk contributed to differences in their uptake kinetics, subsequent interactions with biomolecules, signaling, and responses [1][2][3][10][11][12]22,27,28]. More studies are, therefore, required to confirm this hypothesis.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…However, the mechanism through which ZnO-NP is capable of conferring partly differential responses remains controversial. A majority of researchers believe that differential physicochemical characteristics of nanoparticles relative to the bulk contributed to differences in their uptake kinetics, subsequent interactions with biomolecules, signaling, and responses [1][2][3][10][11][12]22,27,28]. More studies are, therefore, required to confirm this hypothesis.…”
Section: Plos Onementioning
confidence: 99%
“…Transcription factors and mitogen-activated protein kinases (MAPKs) are regulatory proteins that contributed to gene regulation and signal transduction [21,22]. We, therefore, attempted to monitor the ZnO-NP-mediated transcriptional variation in several important transcription factors, including R2R3MYB [23], bHLH [24], WRKY1 [21], EREB [9], HsfA1a [25], and MKK2 [26].…”
Section: Introductionmentioning
confidence: 99%
“…ZnO NPs also induced genes that contributed to the antioxidant system, such as OsCATA , OsCATB , OsPRX65 , OsPRX89 , OsPRX11 , OsCu / ZnSOD1 , OsCu / ZnSOD2 , and OsCu / ZnSOD3 [ 7 ]. The involvement of microRNAs in plant responses to nanoparticles has been supported in barley [ 11 ] and tomato [ 24 ]. It has been well confirmed that microRNAs have close crosslinks with transcription factors and chromatin remodeling systems [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Se nanoparticles in the range of 10 to 30 mg l − 1 exhibited acute toxic effects and alleviated the growth of roots and leaves in Capsicum annuum whilst nSe in the range between 0.5 to 1 mg l − 1 exhibited promotion in the said parameters and also regulated the expression of WRKY1 and bZIP1 transcription factors in DNA methylation techniques (Sotoodehnia-Korani et al, 2020). In the study of Neysanian et al, (2020), it was also reported that 3 mg l − 1 nSe application not only increased the growth, biomass contents and fruit development but also triggered the expression of bZIP transcription factor as well as miR172 gene regulation in tomato plants.…”
Section: Comparison Of Si and Se Based Treatment Effectsmentioning
confidence: 99%